Algunos aspectos morfologicos y agronomicos de otras especies de Phaseolus. Posibilidades para hibridacion interespecifica - Debouck, Daniel G. (International Center for Tropical Agriculture, 1979)
The morphological and agronomic aspects of the species Phaseolus vulgaris, Phaseolus lunatus, Phaseolus coccineus subesp. coccineus and Phaseolus acutifolius var. latifolius are described and the general characters of wild species are also presented. A list of wild species is included along with historical aspects of taxonomic classification and an analysis is given on the changes occurred, genetic distances and the possibilities of hybridization among ancestral and cultivated forms of the 4 species mentioned, and various characters considered valuable for classification within the genus. (CIAT)